2006
DOI: 10.3354/meps321227
|View full text |Cite
|
Sign up to set email alerts
|

Community composition and diet of fishes as a function of tidal channel geomorphology

Abstract: We examined how channel system order and complexity influence fish community composition, abundance, and diet, by comparing first-through fourth-order channel systems at China Camp Marsh, San Francisco Estuary, California, USA. We sampled 6 channel systems (with replicates of the second-and fourth-order systems) bimonthly from July 2001 to May 2002 using modified fyke nets. We examined the diet of the 3 most common species that occurred consistently over time (seasonally): Atherinops affinis, Menidia beryllina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 48 publications
3
30
1
Order By: Relevance
“…planktonic copepods at night and insects during the day) (Stickney & McGeachin 1978, Moyle 2002, our study showed a greater input of potentially autochthonous prey than previous studies. Yellowfin goby diet composition in our study was more consistent with that found in previous studies in their natural range (Kanou et al 2004) and in San Francisco Estuary (Simenstad et al 1999, Grimaldo et al 2004, Visintainer et al 2006. Yellowfin goby diets were more varied and higher in taxa richness than Mississippi silverside diets and contained predominantly benthic or epibenthic prey, including gammarid amphipods, cumaceans, tanaids and polychaete worms.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…planktonic copepods at night and insects during the day) (Stickney & McGeachin 1978, Moyle 2002, our study showed a greater input of potentially autochthonous prey than previous studies. Yellowfin goby diet composition in our study was more consistent with that found in previous studies in their natural range (Kanou et al 2004) and in San Francisco Estuary (Simenstad et al 1999, Grimaldo et al 2004, Visintainer et al 2006. Yellowfin goby diets were more varied and higher in taxa richness than Mississippi silverside diets and contained predominantly benthic or epibenthic prey, including gammarid amphipods, cumaceans, tanaids and polychaete worms.…”
Section: Discussionsupporting
confidence: 81%
“…Even less difference was found in growth rates of Mississippi silversides, which did not significantly vary between either year or wetland type. Diet composition of Mississippi silversides in this study was somewhat different than that found in previous studies of these fish in both their native habitats (Stickney & McGeachin 1978) and elsewhere in San Francisco Bay (Simenstad et al 1999, Grimaldo et al 2004, Visintainer et al 2006. Our expectation for the highly motile, transient Mississippi silverside was that the diet of these fish would be primarily plankton with some input from terrestrial neustonic insects.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…However, the zooplankton communities of tidal marshes of the SFE have never been reported. Given that zooplankton are important prey items for many larval and adult fish in the SFE (Meng & Orsi 1991, Moyle et al 1992, Nobriga 2002, Bollens & Sanders 2004, Visintainer et al 2006, Cohen & Bollens 2008, Howe et al 2014, Whitley & Bollens 2014), a need exists to investigate the basic ecology of tidal marsh zooplankton. More specifically, if the composition and abundance of zooplankton in tidal marshes are found to be suitable prey resources for fish and other higher-level consumers, this could provide a critical link between shallow water habitats (Brown 2003, Lopez et al 2006) and conservation and restoration of pelagic species in the SFE (Sommer et al 2007, Moyle 2008, Mac Nally et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, tidal creeks are involved in the trophic transfer of energy between the marsh surface and adjacent open water (Kneib 2002). The suitability of creeks for nekton utilization is reportedly dependent on specific physical parameters, including flow, depth, location, and other geomorphologial factors (Rozas 1992, Williams & Zedler 1999, Visintainer et al 2006, Allen et al 2007). For example, sloped banks of marsh creeks are conducive to more abundant nekton populations , Rozas 1992, Allen et al 2007.…”
Section: Introductionmentioning
confidence: 99%